2017
DOI: 10.1111/jace.15088
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric performance of SnTe with ZnO carrier compensation, energy filtering, and multiscale phonon scattering

Abstract: In this work, the thermoelectric properties of SnTe have been regulated synergistically by introduction of n‐type ZnO nanoinclusions. On one hand, the excessive holes in SnTe matrix were compensated properly by n‐type ZnO, and the Seebeck coefficient has been improved greatly due to the carrier energy filtering effect by a large quantity of ZnO‐SnTe hetero‐junction interface barriers; On the other hand, the thermal conductivity gets reduced by the enhanced phonon scattering from multiscale hierarchical archite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…In general, SnTe‐based p‐type chalcogenides are known for their high hole density (≈10 20 –10 21 cm −3 ); therefore, EF is made possible in this system. Zhou et al incorporated ZnO particles in a SnTe matrix and observed surprising results . The wide bandgap ZnO phase forming a hole‐blocking layer in the SnTe matrix increases the Seebeck coefficient.…”
Section: Applications Of the Energy Filtering Effect To Different Clamentioning
confidence: 99%
See 2 more Smart Citations
“…In general, SnTe‐based p‐type chalcogenides are known for their high hole density (≈10 20 –10 21 cm −3 ); therefore, EF is made possible in this system. Zhou et al incorporated ZnO particles in a SnTe matrix and observed surprising results . The wide bandgap ZnO phase forming a hole‐blocking layer in the SnTe matrix increases the Seebeck coefficient.…”
Section: Applications Of the Energy Filtering Effect To Different Clamentioning
confidence: 99%
“…This forms a potential well that traps charge carriers. Thus, S was found to increase with increasing temperature due to the mixed effects of the charge carrier EF and charge compensation . Liu et al have recently modified the concept of electron MFP in p‐type SnTe: nanostructures with typical dimensions less than 10 nm can filter‐out easily the long‐MFP electrons.…”
Section: Applications Of the Energy Filtering Effect To Different Clamentioning
confidence: 99%
See 1 more Smart Citation
“…Best performing oxide‐based materials highlighting (A) highest σ, (B) low κ t and (C) ZT value via miscellaneous optimization techniques …”
Section: High Performance Inorganic Te Materialsmentioning
confidence: 99%
“…The excellent TE performance could be realized by increasing the power factor (PF = a 2 s) or compressing the thermal conductivity as much as possible. [6][7][8] Usually, several strategies such as resonant doping, 9,10 band convergence [11][12][13] and carrier concentration optimization 14,15 can effectively increase the power factor, while the lattice thermal conductivity k l can be reduced by the all-scale hierarchical structuring [16][17][18][19] and dense defects [20][21][22][23] as phonon scattering centers.…”
Section: Introductionmentioning
confidence: 99%